2016
DOI: 10.1155/2016/8932908
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrosynthesis of Graphene Oxide-Doped Polypyrrole Nanocomposite as a Nanointerface for Electrochemical Impedance Detection of Cell Adhesion and Proliferation Using Two Approaches

Abstract: A novel nanointerface of graphene oxide-doped polypyrrole (GO/PPy) is prepared on the surface of an indium tin oxide (ITO) electrode for electrochemical impedance detection of cell adhesion and proliferation through a facile one-step electropolymerization. The prepared GO/PPy nanocomposite had a robust surface and provided a biocompatible substrate for A549 cells adhesion and proliferation. The adhesion and proliferation of A549 cells on the surface of the GO/PPy modified ITO electrode directly increased the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Structural configuration analysis and the characteristic vibrational bands of the components (GO, RGO, SRGO, and PPy) and their composites (PPy/GO, PPy/RGO, PPy/SRGO) were characterized using FT-IR spectroscopy in the range of 4000–400 cm –1 (Figure ). The peaks at 1542 and 1457 cm –1 for PPy are assigned to the C–N and C–C stretching vibrations of the pyrrole ring, respectively. , The broad band at 3417 cm –1 is attributed to the N–H stretching vibration . The FT-IR spectrum of GO shows a peak at 1727 cm –1 , which is attributed to the CO stretching of the carboxylic groups present at the edges of the GO sheets .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural configuration analysis and the characteristic vibrational bands of the components (GO, RGO, SRGO, and PPy) and their composites (PPy/GO, PPy/RGO, PPy/SRGO) were characterized using FT-IR spectroscopy in the range of 4000–400 cm –1 (Figure ). The peaks at 1542 and 1457 cm –1 for PPy are assigned to the C–N and C–C stretching vibrations of the pyrrole ring, respectively. , The broad band at 3417 cm –1 is attributed to the N–H stretching vibration . The FT-IR spectrum of GO shows a peak at 1727 cm –1 , which is attributed to the CO stretching of the carboxylic groups present at the edges of the GO sheets .…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 1542 and 1457 cm −1 for PPy are assigned to the C−N and C−C stretching vibrations of the pyrrole ring, respectively. 35,36 The broad band at 3417 cm −1 is attributed to the N−H stretching vibration. 37 The FT-IR spectrum of GO shows a peak at 1727 cm −1 , which is attributed to the CO stretching of the carboxylic groups present at the edges of the GO sheets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The signal at 1703 cm −1 is due to the out-of-plane wagging of the carbonyl group. At 1035 cm −1 , the stretching vibration of C-H of the Py ring can be noticed [30,31]. The peak at 1291 cm −1 is connected to C-N in a plane.…”
Section: Uv-visible Analysis Of the Synthesized Ppy And Ppy/ga Compos...mentioning
confidence: 99%
“…Sodium dodecyl benzenesulfonate (DBS) was usually doped into PPy for many tissue engineering fields, including nerve regeneration, because of the biocompatibility, doping stability, and higher conductivity in PPy. To further improve the conductivity of nerve repair materials, researchers have also applied graphene and its derivatives to biomaterials in recent years, including graphene oxide (GO) and carboxyl functionalized graphene oxide (CFGO) because of their good conductivity and modulation of cellular behavior, leading to the preparation of the conductive PPy materials doped with graphene or its derivatives. , Yan et al reported that polypyrrole/graphene electrodes via electrical stimulation could improve neurite outgrowth and antiaging ability of retinal ganglion cells . And Feng et al.…”
Section: Introductionmentioning
confidence: 99%
“…22−24 To further improve the conductivity of nerve repair materials, researchers have also applied graphene and its derivatives to biomaterials in recent years, including graphene oxide (GO) and carboxyl functionalized graphene oxide (CFGO) because of their good conductivity and modulation of cellular behavior, 25−28 leading to the preparation of the conductive PPy materials doped with graphene or its derivatives. 29,30 Yan et al reported that polypyrrole/graphene electrodes via electrical stimulation could improve neurite outgrowth and antiaging ability of retinal ganglion cells. 29 And Feng et al found that the graphene nanofibers could accelerate the nerve growth via electrical stimulation.…”
Section: ■ Introductionmentioning
confidence: 99%